Arc ubiquitination regulates endoplasmic reticulum-mediated Ca2+ release and CaMKII signaling - Ghane, Mohammad A.; Wei, Wei; Yakout, Dina W.; Allen, Zachary D.; Miller, Cassandra L.; Dong, Bin; Yang, Jenny J.; Fang, Ning; Mabb, Angela M. (Frontiers in Cellular Neuroscience, 2023)
Synaptic plasticity relies on rapid, yet spatially precise signaling to alter synaptic strength. Arc is a brain enriched protein that is rapidly expressed during learning-related behaviors and is essential for regulating metabotropic glutamate receptor-mediated long-term depression (mGluR-LTD). We previously showed that disrupting the ubiquitination capacity of Arc enhances mGluR-LTD; however, the consequences of Arc ubiquitination on other mGluR-mediated signaling events is poorly characterized. Here we find that pharmacological activation of Group I mGluRs with S-3,5-dihydroxyphenylglycine (DHPG) increases Ca2+ release from the endoplasmic reticulum (ER). Disrupting Arc ubiquitination on key amino acid residues enhances DHPG-induced ER-mediated Ca2+ release. These alterations were observed in all neuronal subregions except secondary branchpoints. Deficits in Arc ubiquitination altered Arc self-assembly and enhanced its interaction with calcium/calmodulin-dependent protein kinase IIb (CaMKIIb) and constitutively active forms of CaMKII in HEK293 cells. Colocalization of Arc and CaMKII was altered in cultured hippocampal neurons, with the notable exception of secondary branchpoints. Finally, disruptions in Arc ubiquitination were found to increase Arc interaction with the integral ER protein Calnexin. These results suggest a previously unknown role for Arc ubiquitination in the fine tuning of ER-mediated Ca2+ signaling that may support mGluR-LTD, which in turn, may regulate CaMKII and its interactions with Arc.